Cover Feature: Highly Proton‐Conductive Zinc Metal‐Organic Framework Based On Nickel(II) Porphyrinylphosphonate (Chem. Eur. J. 45/2019). Issue 45 (2nd July 2019) - Enakieva, Yulia Y.; Sinelshchikova, Anna A.; Grigoriev, Mikhail S.; Chernyshev, Vladimir V.; Kovalenko, Konstantin A.; Stenina, Irina A.; Yaroslavtsev, Andrey B.; Gorbunova, Yulia G.; Tsivadze, Aslan Y.
Abstract : A new highly proton‐conductive anionic porphyrinylphosphonate‐based MOF is reported. The artwork presents the view through the channel coated with dimethylammonium (DMA) counterions and uncoordinated oxygen atoms of phosphonate groups, responsible for high proton conductivity of the new material. This property is depicted by the airplane which takes off from the "runway" formed by DMA cations. More information can be found in the Communication by Y. Y. Enakieva et al. on page 10552 .